Soil fertility, system productivity and economic viability of coconut based high density multi species cropping system in Tamil Nadu, India - Sudhalakshmi, C.; Rajakumar, D.; Rani, S.; Maheswarappa, H.P. (Journal of Plantation Crops, 2021)
Monocropping of coconut is no longer viable in the context of price aberrations of copra, debilitating pests and dreadful diseases and intercropping turned out to be an inevitable venture. A research experiment was pursued at the AICRP (Palms) centre, Coconut Research Station, Aliyarnagar, Tamil Nadu, India during 2013-18 to assess the impact of coconut based High Density Multi Species Cropping System (HDMSCS) with cocoa (CCRP accessions), banana (var. Nendran) and pineapple (var. Kew), on soil fertility, system productivity and economic viability. The experiment was conducted in a sandy clay loam soil taxonomically classified as Typic Haplustepts. Four treatments viz., T1: 75 per cent recommended dose of nutrients (RDN) as chemical fertilizers 25 per cent RDN through organic recycling with vermicompost, vermiwash application, biofertilizer application and green manuring with gliricidia loppings; T2: 50 per cent RDN as chemical fertilizers with 50 per cent RDN through organic sources, T3: 100 per cent RDN through organic sources and T4: sole chemical fertilization were imposed in blocks comprising of 25 coconut palms per block. Results revealed that integration of 75 per cent recommended dose of nutrients (RDN) through chemical fertilizers and 25 per cent through organic sources (T1) resulted in increased nut yield of coconut, dry bean yield of cocoa and fruit yield of banana and pineapple. Nut yield was conspicuously lower in monocropping compared to HDMSCS. Soil organic carbon (SOC), earthworm count and microbial population were higher in the treatment, which received 100 per cent RDN through organic sources (T3). Net Returns, B: C ratio and employment generation potential were higher in HDMSCS than coconut monoculture. Partitioning of the recommended dose of nutrients through 75 per cent chemical fertilizers and 25 per cent organic manures for coconut based high density multi species cropping integrated with cocoa, banana and pineapple paved the way for enhanced soil fertility, system productivity, profitability and sustainability of coconut system in Western Zone of Tamil Nadu, India.